(3cjajI GdJZdH Ydi GdQchO GdEbJUGOj (B/s - (3JTShQK, fjcjs; (3GdYGeQj, NGdO s ((3GdbGgQI(B: s (3OGQ GdaGQhb ddfTQ hGdJhRjY(B, s, 2001)
(3GdKHGJ hbJ GdCReGJ(B- (3CKQ GdQchO GdEbJUGOj Ydi JLGQJc(B- (3eGgj MGdJc GdeGdjI?(B- (3GdYdGeGJ GdJMPjQjI(B- (3GdSjhdI GdfbOjI gj cd TjF(B- (3JNdU ef GdeUQhaGJ GdEVGajI(B- (3GbJfU GdUabGJ GdeQHMI(B- (3cf MPQG aj LejY JMQcGJc(B- (3GdCQHGM hGdeHjYGJ(B- (3GeG GdHfc hEeG GdEadGS(B- (3MeGjI CehGdc GdTNUjI(B- (3EP de jadM cd eG SHb(B.s
Keywords: (3GdCReI GdEbJUGOjIs; (3GdQchO GdEbJUGOjs